2017
DOI: 10.5114/aoms.2016.64044
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal lavage examination as a prognostic tool in cases of gastric cancer

Abstract: IntroductionPeritoneal tumor seeding is a common form of recurrence after gastric cancer surgery. The finding of free tumor cells and/or elevation of tumor markers in the peritoneal fluid could predict intraperitoneal tumor recurrence. The results of these examination can be used for indication of aggressive treatment modalities such as hyperthermic intraperitoneal chemotherapy (HIPEC).Material and methodsWe have operated on 105 patients suffering from gastric cancer. The control group consisted of 12 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Despite the significant progress in therapeutic options, including surgery, chemotherapy, and radiotherapy, treatment results are still very poor. Advanced disease with lymph node involvement and remote metastases, which is most commonly diagnosed in Central/Eastern Europe [2, 3], is still a challenge for surgeons and oncologists. Resistance to chemotherapy/radiotherapy mostly contributes to treatment failure in advanced GC.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant progress in therapeutic options, including surgery, chemotherapy, and radiotherapy, treatment results are still very poor. Advanced disease with lymph node involvement and remote metastases, which is most commonly diagnosed in Central/Eastern Europe [2, 3], is still a challenge for surgeons and oncologists. Resistance to chemotherapy/radiotherapy mostly contributes to treatment failure in advanced GC.…”
Section: Introductionmentioning
confidence: 99%
“…The tunnels of adjacent connexons on the plasma membranes of corresponding connected cells form direct channels between the cells. This tiny pipe-type channel is composed of six sub-units and the shifting of the six sub-units turns on or turns off the channel [19,22]. Through observing normal and cancerous gastric tissue ultrastructure via electron microscopy, we observed that the normal gastric mucosal gap junction structure is complete, whereas the gap junction structure of gastric cancer is damaged, and the poorly differentiated gastric cancer tissue's gap junction structure has a greater degree of damage.…”
Section: Discussionmentioning
confidence: 92%
“…These factors may contribute to tumor occurrence [15][16][17][18]. Due in part to this possibility, with the consideration that cancer, associated with many concerns, has long been a major public health problem worldwide [6,14,[19][20][21], gap junctions and gap junction protein have become hot topics in current bioscience research. This study investigated the changes in gap junction ultrastructure and Cx43 in normal gastric tissue and in carcinomatous gastric tissue at different degrees of differentiation in order to provide a novel research direction for gastric cancer pathogenesis as well as to provide potential targets for drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, percutaneous or surgical peritoneal lavage may be performed for early diagnosis of human diseases by encouraging positive results in animal experiments. In some recent studies, percutaneous peritoneal lavage sampling has been used for rapid staging in patients with stomach and pancreatic cancer [ 22 , 23 ]. The routine mesenteric ischemia model with ligation was used here, and the markers may be expressed differently in the model than the clinic.…”
Section: Discussionmentioning
confidence: 99%